Early intervention in the management of pulmonary arterial hypertension: clinical and economic outcomes - Burger CD; Ghandour M; Padmanabhan Menon D; Helmi H; Benza RL (Dove Medical Press, 2017)
Charles D Burger,1 Mohamedanwar Ghandour,1 Divya Padmanabhan Menon,2 Haytham Helmi,3 Raymond L Benza4 1Division of Pulmonary, Allergy and Sleep Medicine, Mayo Clinic, 2Department of Internal Medicine, Mayo Clinic, 3Division of Transplant Medicine and Research Administration, Mayo Clinic, Jacksonville, FL, USA; 4Advanced Heart Failure, Transplant, Mechanical Circulatory Support and Pulmonary Hypertension, Allegheny Health Network, Pittsburg, PA, USA Abstract: Pulmonary arterial hypertension (PAH) has a high morbidity rate and is fatal if left untreated. Increasing evidence supports early intervention, possibly with initial combination therapy. PAH-specific pharmaceuticals, however, are expensive and may have serious adverse effects, particularly when used in combination. The currently dynamic health care economy reinforces the need for a review of early intervention from both outcomes and economic perspectives. We aimed to review the clinical and economic impact of PAH therapy, particularly examining drug cost, hospitalization burden, and health care economics impact, and the effect of early intervention on clinical outcomes. We searched PubMed, Scopus, Ovid, and MEDLINE databases from 2005 to 2017 for studies comparing drug cost, clinical outcomes, and hospitalization burden associated with therapy for PAH. Emerging data indicate that early therapy is effective, but drug therapy is expensive, particularly with combination therapy. Efficacy studies also generally show benefit of combination therapy for patients in World Health Organization functional class II, with a consistent decrease in hospitalization. Pharmacoeconomic studies are limited but indicate that increased pharmacy costs are at least partially offset by decreased health care utilization, particularly inpatient care. Modeling also shows a cost benefit with combination therapy at 2 years. Nonetheless, more rigorously collected health care economic data should be incorporated into future drug efficacy trials to provide a clearer understanding of the impact and the associated cost benefit of early PAH therapy. Increasing evidence in support of early intervention and combination therapy for PAH is associated with rising medication costs that are largely offset by reduced hospitalization, on the basis of the currently available literature. Nonetheless, the studies performed to date have methodologic limitations that highlight the need for prospective studies using more robust economic modeling. Keywords: combination therapy, health care costs, hospitalization, pulmonary arterial hypertension